2023
DOI: 10.3390/life13041046
|View full text |Cite
|
Sign up to set email alerts
|

Critical Assessment of the Anti-Inflammatory Potential of Usnic Acid and Its Derivatives—A Review

Abstract: Inflammation is a response of the organism to an external factor that disrupts its natural homeostasis, and it helps to eliminate the cause of tissue injury. However, sometimes the body’s response is highly inadequate and the inflammation may become chronic. Thus, the search for novel anti-inflammatory agents is still needed. One of the groups of natural compounds that attract interest in this context is lichen metabolites, with usnic acid (UA) as the most promising candidate. The compound reveals a broad spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Studies have shown that lichen metabolites contain biologically active compounds that possess anti-COX-2 activity [ 53 , 54 , 55 ]. Based on the results of in vivo studies, lichen extracts can inhibit the inflammatory response in animal tissue [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that lichen metabolites contain biologically active compounds that possess anti-COX-2 activity [ 53 , 54 , 55 ]. Based on the results of in vivo studies, lichen extracts can inhibit the inflammatory response in animal tissue [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Usnic acid (UA), a dibenzofuran produced from lichen, is one of them [ 113 ]. Usnic acid is able to reduce the inflammation related to burns and to encourage wound closure through keratinocyte monolayers [ 64 , 114 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies showed that UA has an antimicrobial effect against anaerobic bacteria such as Bacteroides ruminicola ssp. Brevis , Bacteroides fragilis , Bacteroides vulgatus [ 63 , 64 ], Clostridium perfringens [ 63 , 64 , 65 ], Propionibacterium acnes [ 63 , 64 , 65 ], Bacteroides thetaiotaomicron [ 63 , 64 ], Gram-positive bacteria such as Enterococcus faecium [ 63 , 64 ], Enterococcus faecalis [ 63 , 64 , 65 ], Staphylococcus aureus [ 64 , 65 , 66 , 67 ], S. mutans [ 68 , 69 , 70 , 71 ], S. epidermidis [ 63 , 65 , 72 ], Streptococcus pyogenes [ 63 , 64 , 73 , 74 ], Streptococcus pneumoniae [ 64 , 65 ], Gram-negative bacteria such as Escherichia coli , Haemophilus influenza , Pseudomonas aeruginosa , and Mycobacteria such as M. aurum , M. avium , M. smegmatis , M. tuberculosis var. bovis , M. tuberculosis var.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been stated that Usnea longissima extracts have strong antioxidant effects [21]. Also, it has been shown that usnic acid, a metabolite of Usnea longissima, inhibits in ammation both in vitro and in vivo [22]. This information obtained from the literature suggests that extracts obtained from Usnea longissima may be useful in the treatment of doxorubicin and cisplatin-related multi-organ toxicity.…”
Section: Introductionmentioning
confidence: 99%